Glutathione-dependent system in the blood of gastric cancer patients with various tumor histotypes and prevalence of the disease - I. A. Goroshinskaya; E. I. Surikova; E. M. Frantsiyants; L. A. Nemashkalova; P. S. Kachesova; D. E. Medvedeva; A. A. Maslov (Исследования и практика в медицине)
Purpose of the study. Exploring the erythrocyte glutathione system functioning in patients with gastric cancer in a comparative aspect, depending on tumor histotype and disease prevalence.Patients and methods. The study included 89 patients with gastric cancer, divided into 6 groups depending on the histotype of the tumor. Separately, the results of the study were analyzed in patients with T4 status according to TNM and in patients at stage 4. The content of reduced glutathione and the activity of glutathione-dependent enzymes in the erythrocytes of the patients' blood were studied by conventional spectrophotometric methods. Statistical processing of the results was carried out using the Statistika 6.0 software package according to the Student's t-test and the nonparametric Wilcoxon-Mann-Whitney test for two independent samples.Results. An increase in the content of glutathione was revealed in patients with gastric cancer compared with the group without oncopathology. The maximum increase was observed in patients with low-grade adenocarcinoma - by 42.5 %, while in signet ring cell carcinoma (SRCC) there was only a tendency to increase by 17.8 %. Glutathione reductase activity was decreased in adenocarcinoma by 23.4-26.2 % and did not change in SRCC. The activity of the antioxidant enzymes glutathione peroxidase and glutathione transferase was increased in all groups, and especially in SRCC - by 76 % and 23-29 %, respectively. In patients with the T4 status and at stage IV of the process, a lower activity of the studied glutathione-dependent enzymes was revealed in comparison with all other groups of patients.Conclusions. The data obtained indicate a greater functional potential of the glutathione system in SRCC. A significant increase in glutathione transferase activity at a sufficiently high level of reduced glutathione can contribute to the development of treatment resistance in SRCC patients.